Characterization of titanium surface coated with epidermal growth factor and its effect on human gingival fibroblasts - Pansani, Taisa Nogueira [UNESP]; Basso, Fernanda Gonçalves; Souza, Isabela dos Reis [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Elsevier, 2019)
Objectives: Different strategies, such as modifications on the implant abutments surface have been proposed to accelerate and improve the formation of the biological seal (BS). The aim of this study was to characterize a titanium (Ti) surface impregnated with epidermal growth factor (EGF) and to assess its influence on the metabolism and adhesion of oral mucosal cells. Design: Ti discs were coated with EGF (100 nM) conjugated with a fluorophore and analyzed by fluorescence microscopy. The surface roughness analysis (Ra) of the EGF-coated Ti was performed by confocal microscopy. The EGF released in the wet environment was determined at 0, 24, 48 and 72 h by fluorimetric quantification. For assessment of the biological effects of EGF-coated Ti, gingival fibroblasts were seeded (5 × 10 4 cells) onto the substrate coated or not with this growth factor. After 24 h, cell adhesion and viability were evaluated by ANOVA and Tukey tests, α =.05. Results: Immediate release of EGF as well as its incorporation by fibroblasts within 1 h after cells were seeded was observed. EGF-coated Ti discs presented significantly enhance surface roughness. Increased cell viability was observed on the EGF-coated discs. Conclusion: EGF applied to Ti discs stimulated the adhesion and metabolism of gingival fibroblasts and could be considered as an interesting alternative for improving the BS.
Keywords: Abutment; Cell survival; Epidermal growth factor; Fibroblast; Titanium